Preparation and Properties of Luminomagnetic Nanoparticles with Magnetic Core and Terbium Complex Shell - Lu, Ruihua; He, Jiang; Ge, Xia; Huang, Lizhen; Zhu, Jie; Du, Xiaoyan (Asian Journal of Chemistry, 2011)
Novel luminomagnetic nanoparticles with magnetic core and terbium complex shell have been developed using a modified Stöber method combined with a layer-by-layer assembly process. Fe3O4 nanoparticles as the magnetic core were firstly coated by a silica shell. Then, a kind of modified monomer (abbreviated as SA-Si) synthesized by grafting the coupling agent 3-isocyanatepropyltriethoxysilane (ICPTES) to salicylic acid (SA) was used as the ligand for coordination with Tb3+ ions. The ternary Tb3+ complex (denoted as SA-Si-Tb) served as the luminescent marker was covalently bonded to the silica surface. Subsequently, an outer shell of silica was introduced to allow for versatile surface functionalities. The architecture has been characterized by Fourier transform infrared spectra (FT-IR), transmission electron microscopy (TEM), vibration sample magnetometer (VSM) and photoluminescence (PL) spectra. The resultant luminomagnetic nanoparticles exhibited favourable superparamagnetic behaviour and photoluminescence properties, which had potential application in biolabelling, bioseparation, immunoassay and pathogenic diagnosis.